Answer:
don't know
Step-by-step explanation:
B) Liter
C) Gram
D) Meter
Answer:
Diapers costs $11 and formula is $13.
Step-by-step explanation:
Let's name diapers as A and formula as B.
Simply the equations:
1A + 2B = $37(1)
2A + 5B = $87(2)
Clear D from one equation.
A = $37 - 2B(1)
Replace D into the other equation.
2*($37 - 2B) + 5B = $87(2)
$74 - 4B + 5B = $87
$74 + B = $87
B = $87 - $74 = $13
Find A, now knowing B.
A = $37 - 2($13)
A = $37 - $26 = $11
Answer:
Cost of a bag of diapers is $11 and cost of one can of formula is $13.
Step-by-step explanation:
Let cost of each diaper = $D and cost of each cans of formula = $C
Malik shops a bag of diapers and 2 cans of formula.
He spends total of $37.
So the equation will be
D + 2C = 37 -------(1)
Next week he stops and buys 2 bags of diapers and 5 cans of formula.
He spends total $87.
Equation for this purchase will be
2D + 5C = 87 ----------(2)
Multiply equation (1) by 2 and subtract it from equation (2).
2(D + 2C) - (2D + 5C) = 2×37 - 87
2D + 4C - 2D - 5C = 74 - 87
-C = - 13
C = 13
From equation (1)
D + 2×13 = 37
D + 26 = 37
D = 37 - 26
D = 11
Therefore, cost of a bag of diapers is $11 and cost of one can of formula is $13.
Check all that apply.
2x2 +9x + 4 = 0
Answer:
Step-by-step explanation:
Use quadratic formula:
x=((-b+-sqrt(b^2-4ac))/2a
x=((-9+-sqrt(9^2-4(2)(4))/2(2)
x=((-9+-sqrt(81-32))/4
x=((-9+-sqrt(49))/4
x=(-9+-7)/4
Solution 1:
x=-2/4
x=-1/2
Solution 2:
x=-16/4
x=-4
Now we check:
2(-1/2)^2+9(-1/2)+4=2/4+-9/2+4=1/2+-9/2+4=-8/2+4=-4+4=0 (x=-1/2 works)
2(-4)^2+9(-4)+4=2(16)+(-36)+4=32-36+4=-4+4=0 (x=-4 works)
So the solutions of the equation are x=-1/2 and x=-4
in this case
a=2 b=9 c4
for this equation we have the formula
x1/2 = (-b +- (root of) b2 -4ac) /2a
x1/2 = (-9 +- (root of) 81- 4×2×4)/2×2
x1/2= (-9 +- (root of) 81-32)/4
x1/2 = (-9 +- (root of) 49/4
x1/2 = (-9 +- 7)/4
x1= -9+7/4
x1=-2/4
x1=-1/2
x2= -9-7/4
x2= -16/4
x2= -4